1993
DOI: 10.1103/physrevb.48.15787
|View full text |Cite
|
Sign up to set email alerts
|

Chern-Simons gauge field theory of two-dimensional ferromagnets

Abstract: A Chern-Simons gauged Nonlinear Schrödinger Equation is derived from the continuous Heisenberg model in 2+1 dimensions. The corresponding planar magnets can be analyzed whithin the anyon theory. Thus, we show that static magnetic vortices correspond to the self-dual Chern -Simons solitons and are described by the Liouville equation. The related magnetic topological charge is associated with the electric charge of anyons. Furthermore, vortex -antivortex configurations are described by the sinh-Gordon equation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…It has been shown that the Chern-Simons gauged Landau-Ginsburg model plays the role of effective theory for the Fractional Quantum Hall Effect [2]. The Chern-Simons equation of motion can describe time evolving two-dimensional surfaces in such a way that the deformation is not only locally compatible with the Gauss-Codazzi equation, but completely integrable as well [3].…”
Section: Copyright C 2002 By P Bracken and A M Grundlandmentioning
confidence: 99%
“…It has been shown that the Chern-Simons gauged Landau-Ginsburg model plays the role of effective theory for the Fractional Quantum Hall Effect [2]. The Chern-Simons equation of motion can describe time evolving two-dimensional surfaces in such a way that the deformation is not only locally compatible with the Gauss-Codazzi equation, but completely integrable as well [3].…”
Section: Copyright C 2002 By P Bracken and A M Grundlandmentioning
confidence: 99%
“…This idea has been recently applied to the classical Heisenberg model in [12]. Furthermore, the stationary magnetic vortices of the model have been related to the Chern-Simons solitons, while the topological charge of the former has been related to the electric charge of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…But, as we will see below the mapping of the model (2.1) to zero curvature equations connects these fields. Finally, let us emphasize that if for the Heisenberg model it was sufficient to have SU (2) zero curvature mapping [12], for the model considered here an additional gauge field, related to the velocity field v is necessary. …”
mentioning
confidence: 99%
“…For instance, for Ψ + ≡ 0 we can find Ψ − in terms of solutions of the Liouville equation, to which our system of equations reduces. Such solutions of multivortex type are widely discussed in [9,10].…”
mentioning
confidence: 99%
“…The vorticity is determined by the density of the topological charge. These types of systems have been discussed in [9] - [12]. They can be considered as generalizations of the well-known Ishimori model [13].…”
mentioning
confidence: 99%